Teaching as a system: Insights from a teacher professional development program - Bassi, Caterina; Brunetto, Domenico; Dello Iacono, Umberto (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
The influence of a change in teachers’ practice on teachers’ knowledge and beliefs has seldom been investigated in the literature. In the present work, we aim to explore the influence of a change in practice forced by participating in a Teacher Professional Development (TPD) program on beliefs, knowledge and practice. To this end, we consider the case of Katia, a teacher involved in a TPD program focused on mathematical modelling with digital technologies, and we employ the teaching system model to document the evolution of her practice, beliefs and knowledge. The performed analysis shows a change of practice induced by the TPD program, highlighting its influence on beliefs and the essential role of knowledge in sustaining teachers in further expanding their practice.